(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease that is associated with a severe decline in respiratory ability and the quality of life. The symptoms such as dyspnea, fatigue and loss of physical endurance deteriorate as the disease advances. Techniques Non-pharmacological methods, including the Relaxation Technique of Benson and Tai Chi, have also been examined as ways of controlling these symptoms and enhancing the well-being of patients. Purpose: The purpose of the study was to establish the effectiveness of the Relaxation Technique by Benson and Tai Chi on patients with COPD to improve their dyspnea, physical endurance, and quality of life. Methods: The study was a randomized clinical trial that was carried out in the Victoria Hospital, Bahawalpur, within the period from March, 2025 and the rest of August, 2025. Sixty COPD patients were randomly divided into two groups including Group A (Benson Relaxation Technique) and Group B (Tai Chi). The two interventions were 6-week interventions with normal COPD care. The evaluations of the outcomes were done through the use of the modified Borg Dyspnea Scale (MBDS), 6-Minute Walk Test (6MWT), and St. George Respiratory Questionnaire (SGRQ). The data were evaluated by means of Mann-Whitney U and Wilcoxon Signed Rank tests. Results: The two interventions resulted in significant improvements. Group A experienced a change of dyspnea (MBDS: p < 0.0001) and quality of life (SGRQ: p = 0.028). Group B showed a higher physical endurance (6MWT: p < 0.0001) and less fatigue (MBDS: p < 0.0001). But comparisons of the groups did not find any differences of significance in dyspnea or exercise tolerance. Conclusion: Benson Relaxation Technique and Tai Chi are both effective in managing COPD symptoms; Tai Chi proved to have more beneficial effects on physical performance, whereas Benson method gave more benefits to mental well-being. These interventions can be incorporated in the COPD management plans in order to provide a holistic treatment of patients.